Heterogeneous Patterns of Endothelial NF-κB p65 and MAPK c-Jun Activation, Adhesion Molecule Expression, and Leukocyte Recruitment in Lung Microvasculature of Mice with Sepsis - Zhendong Wang; Erna-Zulaikha Dayang; Peter J. Zwiers; Martha L. Hernandez Garcia; Matthijs Luxen; Matijs van Meurs; Jill Moser; Jan A. A. M. Kamps; Grietje Molema (Biomedicines, 2024)
Background: Sepsis is an uncontrolled systemic inflammatory response to an infection that can result in acute failure of the function of the lung called acute respiratory distress syndrome. Leukocyte recruitment is an important hallmark of acute lung failure in patients with sepsis. Endothelial cells (EC) participate in this process by facilitating tethering, rolling, adhesion, and transmigration of leukocytes via adhesion molecules on their cell surface. In in vivo studies, endothelial nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) p65 and mitogen-activated protein kinase (MAPK) c-Jun intracellular signal transduction pathways were reported to regulate the expression of adhesion molecules. Methods: Mice underwent cecal ligation and puncture (CLP) to induce polymicrobial sepsis and were sacrificed at different time points up to 72 h after sepsis onset. Immunohistochemistry and reverse transcription–quantitative polymerase chain reaction (RT-qPCR) analyses were used to determine the kinetics of nuclear localization of p65 and c-Jun in EC, expression and location of adhesion molecules E-selectin and vascular cell adhesion molecule 1 (VCAM-1). Furthermore, the extent and location of leukocyte recruitment were assessed based on Ly6G staining of neutrophils, cluster determinant (CD) 3 staining of T lymphocytes, and CD68 staining of macrophages. Results: In all pulmonary microvascular beds, we identified p65 and c-Jun nuclear accumulation in a subset of endothelial cells within the first 24 h after CLP-sepsis initiation. E-selectin protein was expressed in a subset of microvessels at 4 and 7 h after sepsis initiation, while VCAM-1 was expressed in a scattered pattern in alveolar tissue and microvessels, without discernible changes during sepsis development. CLP-induced sepsis predominantly promoted the accumulation of neutrophils and T lymphocytes 4 and 7 h after disease onset. Neutrophil accumulation occurred in all pulmonary microvascular beds, while T lymphocytes were present in alveolar tissue and postcapillary venules. Taken together, nuclear localization of p65 and c-Jun in EC and neutrophil recruitment could be associated with induced E-selectin expression in the pulmonary microvessels in CLP-septic mice at the early stage of the disease. In alveolar capillaries, on the other hand, activation of these molecular pathways and leukocyte accumulation occurred in the absence of E-selectin or VCAM-1. Conclusions: Endothelial activation and leukocyte recruitment in sepsis-induced lung injury are regulated by multiple, heterogeneously controlled mechanisms, which vary depending on the type of microvascular bed involved.